To See or Not To See: Preservice Teacher Attitudes Toward Color Blindness. Issue 2 (2nd April 2016) - Kreamelmeyer, Kathleen; Kline, Anthony; Zygmunt, Eva; Clark, Patricia
Abstract : This study examined the perspectives of 85 undergraduate preservice teacher candidates engaged in a required survey course on diversity at a midsized Midwestern university. Candidates completed the Common Beliefs Survey at both the beginning and end of the 16-week semester. Quantitative analysis of the pre- and postcourse Likert ratings of candidates indicated a significant negative shift relative to the statement, "I don't think of my students in terms of their race or ethnicity; I am color-blind when it comes to my teaching." Further qualitative analysis of candidates who provided written rationale for their numeric response indicated prevailing themes of conscious bias, intentional color-blindness, and movement toward appreciation of racial difference as a critical cognizance. Implications for teacher education include experiences beyond the scope of a survey course if significant schematic shift leading to the potential for educational equity is to be realized .